Between Pedagogical Therapy and Educational Support for Pupils: Discussion on Terminology and Professional Interventions in the Concept and Implementation of Inclusive Education - Baran, Jolanta (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2021)
The presented text reflects on the actions, understanding and use of terms related in particular to psychological and pedagogical support and pedagogical therapy and the role of specialists in educational institutions and inclusive teams of students. The considerations refer to the literature of both new and older one in order to compare the different conceptual and implementation of the assistance given to students with the respect to their needs. In conclusion, there have been presented a comparison of the support provided in chosen countries to the students with different developmental potentials, including disabilities, in inclusive education. It was meant in order to draw attention to specific solutions and the terminology used when psychological and pedagogical support is provided for pupils/students within the inclusive school.